DNA BARCODING USING COI GENE SEQUENCES OF WILD BETTA FIGHTING FISH FROM INDONESIA: PHYLOGENY, STATUS AND DIVERSITY - Melta R. Fahmi; Eni Kusrini; Erma P. Hayuningtiyas; Shofihar Sinansari; Rudhy Gustiano (Research Center for Fisheries, 2020)
The wild betta fish is a potential ornamental fish export commodity normally caught by traders or hobbyists in the wild. However, the population of wild betta in nature has declined and become a threat for their sustainability. This research was conducted to analyze the genetic diversity, phylogenetic relationships, and molecular identification through DNA COI gene sequence of Indonesian wild betta fish. A total of 92 wild betta fish specimens were collected in this study. Amplification of COI genes was carried out using Fish F1, Fish R1, Fish F2, and Fish R2 primers. The genetic diversity and phylogenetic relationships were analyzed using MEGA version 5 software program. Species identification of the specimen was conducted using BLAST program with 98-100% similarity value of the DNA sequences to indicate the same species. Phylogenetic tree construction showed seven monophyletic clades and showed that Betta smaragdina was the ancestral species of genus Betta in Indonesian waters. Genetic distance among species ranged from 0.02 to 0.30, whereas intra-species genetic distance ranged from 0 to 6.54.